Degenerative changes in the adjacent segments after stabi¬lizing operations on the vertebral column - Radchenko, Volodymyr; Fedak, Volodymyr; Dedukh, Ninel; Malyshkina, Svitlana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
This analytical review covered 80 scientific publications. Clinical and experimental studies of degenerative changes in adjoining intervertebral disks after spinal fusion were assessed. The part of the following risk factors in the development of diseases in adjoining segments after spinal fusion was revealed and assessed: character of instrumentation (long or short), type of performed stabilization (union), localization of surgical intervention (spinal segment), sagittal imbalance, state of intervertebral disks at the moment of operation, age and sex of patients, state of bone tissue (osteopenia, osteoporosis). Multifactorial etiology of the disease of adjoining segments after spinal fusion was proved.